2021
DOI: 10.3389/fimmu.2021.690698
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of COVID-19 Tozinameran Vaccination in Patients on Chronic Dialysis

Abstract: Patients with kidney failure have notoriously weak responses to common vaccines. Thus, immunogenicity of novel SARS-CoV-2 vaccines might be impaired in this group. To determine immunogenicity of SARS-CoV-2 vaccination in patients with chronic dialysis, we analyzed the humoral and T-cell response after two doses of mRNA vaccine Tozinameran (BNT162b2 BioNTech/Pfizer). This observational study included 43 patients on dialysis before vaccination with two doses of Tozinameran 21 days apart. Overall, 36 patients com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 25 publications
2
67
1
Order By: Relevance
“…The analysis of plasma SARS-CoV-2-specific IgG and IgA showed an overall response to mRNA vaccine in 94.4% dialysis patients, which is comparable to data shown in other reports (70.5-96%) 19,22,41,42 . Nevertheless, we observed reduced antibody levels after both the first and the second dose in HD patients who were naïve to SARS-CoV-2, a finding consistent with a delayed immune response in this population 19,43,44 .…”
Section: Discussionsupporting
confidence: 89%
“…The analysis of plasma SARS-CoV-2-specific IgG and IgA showed an overall response to mRNA vaccine in 94.4% dialysis patients, which is comparable to data shown in other reports (70.5-96%) 19,22,41,42 . Nevertheless, we observed reduced antibody levels after both the first and the second dose in HD patients who were naïve to SARS-CoV-2, a finding consistent with a delayed immune response in this population 19,43,44 .…”
Section: Discussionsupporting
confidence: 89%
“…Thirty-three studies reported immunogenicity in 6302 patients on dialysis ( Table S4 ) [ [15] , [16] , [17] , 21 , 31 , 38 , 44 , [62] , [63] , [64] , 74 , 78 , 80 , [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] ]. Non-responder rates ranged from 2% to 30% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…found a high non-response rate at 27% (22/80), at least partially explained by the choice of a higher cut-off (29 U/mL) than the one provided by the manufacturer of the serological assay [ 118 , 135 ]. Fifteen studies included a control group ( n = 779 overall), in which all but nine participants developed post-vaccine antibodies [ 17 , 21 , 63 , 74 , 78 , 80 , 116 , 118 , 120 , 121 , 124 , 126 , 128 , 131 , 134 ]. Speer et al.…”
Section: Resultsmentioning
confidence: 99%
“…So far, observational reports on SARS-CoV-2 vaccination in chronic hemodialysis patients have shown both, an insufficient immune response [ 11 , 12 ] as well as similar effectiveness when compared to the general population with reported effectiveness rates of >90% after a second dose [ 13 ]. Although the response rate of 82.1% in our multi-center cohort was significantly lower than in the healthy control group (98.3%), SARS-CoV-2 vaccination is by far more effective than the so far reported different other vaccinations e.g., for hepatitis B in this vulnerable patient cohort [ 14 ].…”
Section: Discussionmentioning
confidence: 99%